Blockchain Monitoring at BSI KC Binjai Detects Online Gambling Funds: Pemantauan Blockchain di BSI KC Binjai Mendeteksi Dana Judi Online - Deri Kurniawan; Nurbaiti; Rahmi Syahriza (Academia Open, 2025)
General Background: The rapid development of digital technology, particularly blockchain, has transformed the financial sector by enhancing transaction security and transparency. Specific Background: However, in Indonesia, this advancement faces significant challenges, especially in curbing illegal activities such as online gambling, which infiltrate banking systems, including sharia banks. Knowledge Gap: Despite existing sharia supervisory mechanisms, online gambling transactions still manage to bypass detection in some cases, raising concerns about the effectiveness of current monitoring systems. Aims: This study investigates the implementation of blockchain technology at Bank Syariah Indonesia (BSI) KC Binjai to enhance transaction supervision and prevent unlawful fund flows while maintaining sharia compliance. Results: Using a qualitative descriptive-explorative approach, findings reveal that blockchain has improved real-time monitoring, transparency, and the ability to detect and block suspicious transactions, particularly those linked to online gambling. Novelty: The integration of blockchain with smart contracts, coupled with collaboration among sharia supervisory boards and financial regulators, presents a new systemic approach to reinforcing Islamic banking integrity. Implications: The study highlights the strategic value of blockchain in safeguarding sharia financial systems and offers a replicable model for other Islamic banks to enhance compliance and counter financial crimes.Highlight : Blockchain improves real-time detection and blocking of suspicious transactions, including online gambling. Its transparency and immutability support Sharia compliance in Islamic banking. Effective use requires strong governance, regulation synergy, and user education. Keywords : Blockchain, Transaction Monitoring, Sharia Compliance, Online Gambling, Indonesian Islamic Bank